Prognostic Value of Oral Epstein–Barr Virus DNA Load in Locoregionally Advanced Nasopharyngeal Carcinoma - He, Yong-Qiao; Zhou, Ting; Yang, Da-Wei; Jia, Yi-Jing; Yuan, Lei-Lei; Zhang, Wen-Li; Wang, Tong-Min; Liao, Ying; Xue, Wen-Qiong; Zhang, Jiang-Bo; Zheng, Xiao-Hui; Li, Xi-Zhao; et al. (Frontiers in Molecular Biosciences, 2022)
Background: Plasma Epstein-Barr virus (EBV) DNA load has been widely used for nasopharyngeal carcinoma (NPC) prognosis risk stratification. However, oral EBV DNA load, a non-invasive biomarker that reflects EBV lytic replication activity, has not been evaluated for its prognostic value in NPC yet. Methods: 1,194 locoregionally advanced NPC (LA-NPC) patients from south China were included from a prospective observational cohort (GARTC) with a median follow-up of 107.3 months. Pre-treatment or mid-treatment mouthwashes were collected for EBV DNA detection by quantitative polymerase chain reaction (qPCR). The difference of pre- and mid-treatment oral EBV DNA load was tested by Wilcoxon signed-rank test. The associations of oral EBV DNA load with overall survival (OS), progression-free survival (PFS), distant metastasis-free survival (DMFS), and locoregional relapse-free survival (LRFS) were assessed using the log-rank test and multivariate Cox regressions. Results: High level of oral EBV DNA load (>2,100 copies/mL) were independently associated with worse OS (HR=1.45, 95% CI: 1.20-1.74, P<0.001), PFS (HR=1.38, 95%CI: 1.16-1.65, P<0.001), DMFS (HR=1.66, 95%CI: 1.25-2.21, P=0.001), and LRFS (HR=1.43, 95%CI: 1.05-1.96, P=0.023). Similar and robust associations between oral EBV DNA load and prognosis were observed for patients both in the pre-treatment and mid-treatment stages. The detection rate (71.7 % vs. 48.6%, P<0.001) and the median load of oral EBV DNA (13,368 vs. 382 copies/mL, P<0.001) for patients in the pre-treatment stage were significantly higher than that in the mid-treatment stage. The combination of oral EBV DNA load and TNM staging provided more precise risk-stratification for LA-NPC patients. Conclusions: Oral EBV DNA load was an alternative non-invasive predictor of prognosis and may facilitate risk stratification for LA-NPC patients.